Operations management / Terry Hill. - Hill, Terry, 1940- (Palgrave Macmillan, 2005)
Drawing on his extensive industrial and consultancy experience, Terry Hill balances the strategic role of the operations manager with day-to-day management tasks, and shows how each step and decision in operations is affected by market needs and wants.